2004
DOI: 10.1113/expphysiol.2004.027516
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of renal vascular endothelial growth factor mRNA expression and protein level in post‐ischaemic rat kidneys

Abstract: Vascular endothelial growth factor (VEGF) is a potent regulator of angiogenesis and vascular protection. Synthesis of VEGF is induced by hypoxia and different cytokines including interleukin-6 (IL-6) and interleukin-1β (IL-1β). However, post-ischaemic alterations of this growth factor in the kidney are incompletely known. To determine VEGF synthesis in renal ischaemia/reperfusion (I/R) injury unilateral warm ischaemia was induced by cross-clamping the left renal pedicle for 55 min followed by 2 and 24 h of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
3
22
0
1
Order By: Relevance
“…We observed that, in addition to normal VEGF expression in the outer medulla (48), four of nine cysts in one of the three mice examined expressed VEGF (Fig. 6F).…”
Section: Ref 39)mentioning
confidence: 87%
“…We observed that, in addition to normal VEGF expression in the outer medulla (48), four of nine cysts in one of the three mice examined expressed VEGF (Fig. 6F).…”
Section: Ref 39)mentioning
confidence: 87%
“…VEGF is a growth factor that specifically promotes endothelial cell proliferation, differentiation, and survival, as well as mediating endothelium-dependent vasodilatation, inducing microvascular hyperpermeability, and participating in interstitial matrix remodeling. 38 Although VEGF protein levels have been reported to increase in postischemic rat kidneys, 39 the role of VEGF in human renal pathophysiology has not been clarified. [38][39][40] The possible role of EGF in renal growth or maturation and decreased urinary EGF excretion in children with AKI has been reported.…”
Section: Urinary Markers In Ischemic Acute Kidney Injury 705mentioning
confidence: 99%
“…38 Although VEGF protein levels have been reported to increase in postischemic rat kidneys, 39 the role of VEGF in human renal pathophysiology has not been clarified. [38][39][40] The possible role of EGF in renal growth or maturation and decreased urinary EGF excretion in children with AKI has been reported. 41 Our findings suggest that TGF-a and VEGF may be involved in inflammatory processes and that EGF is involved in regenerative processes in human ischemic AKI.…”
Section: Urinary Markers In Ischemic Acute Kidney Injury 705mentioning
confidence: 99%
“…We favor the investigation of VEGF protein instead of VEGFmRNA, based on a previous observation that VEGF synthesis during ischemia/reperfusion injury is regulated, in the postischemic kidney, at a post-transcriptional rather than at a transcriptional level [14]. The regulation of the two VEGF receptors is equally interesting, as hitherto previously investigated [15].…”
Section: Discussionmentioning
confidence: 99%